Modeling Limit Languages via Limit Adjacency Matrix and Yusof-Goode Approaches - Wen, Li Lim; Yuhani, Yusof (AIP Publishing LLC, 2015)
Limit language was introduced by Goode and Pixton in 2004 under the framework of formal language theory. It is a subset of splicing languages which is restricted to the molecules that will be presented in the splicing system after the reaction of biochemical has run to its completion. In this paper, limit adjacency matrix will be introduced to model the existence of limit languages from splicing languages. Besides, it can be used to characterize the splicing language in terms of active persistent, adult/inert and transient properties based on Yusof -Goode splicing system. In this paper, some examples and theorems that have been formulated via limit adjacency matrix approach will be presented too.